To Evaluate the Effect of Auxin Concentrations (IBA and IAA) on Survival Percentage of Stem Cuttings of Species Terminalia chebula (Retz.) - Babu, Bojja Harish; Larkin, Amit; Kumar, Hemant (Indian Forester, 2019)
The effect of IBA and IAA concentrations were examined to determine the Survival percentage of Terminalia chebula (Retz.) by vegetative propagation via rooting in stem cuttings. The experiment was conducted in a completely randomized design (CRD) with three replications. One-year old leafless branch cuttings were taken from selected superior phenotypes from the surrounding environs of Allahabad, UP. Cuttings were treated with 0, 500, 1000, 1500 and 2000 mg L-1 concentrations of Indole-3-Butyric Acid (IBA) and Indole-3-Acetic Acid (IAA) and planted in poly bags kept under a phyto-environmentally controlled mist chamber. Minimum survival percentage and A limited rooting was achieved in untreated cuttings (control) while survival percentage and rooting of treated cuttings significantly increased with an increase in concentration of IBA and IAA. Among two auxins tested, IBA emerged most effective on survival percentage and in inducing rooting, sprouting and associated traits. Amongst different concentrations of auxins, concentration 2000 mg L-1 was found best and 51.96% of plants were survived and achieved over 70% rooting in cuttings. It also triggered more number of roots, higher root length, shoot proliferation, maximum shoot and root biomass. This paper discusses the role of auxins (IBA and IAA) to evaluate the survival percentage of stem cuttings influencing rooting and has a practical implication for the development of protocol for asexual propagation and establishing clonal plantations of Terminalia chebula.